(3UhQI GdYQH h(B"(3ESQGFjd(B" (3aj GdefGgL GdJQHhjI GdLOjOIs - (3fUQ GdOjf, egi QGeRs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2005)
(3Jbhe GdOQGSI Ydi GdHMK aj GdcJGH GdeOQSj GddHfGfj GdQSej Yf UhQI GdYQH ef LgI hYf UhQI ESQGFjd ef LgI KGfjI, hPdc HgOa eYQaI WHjYI GdUhQ GdJj JbqOe Yf GdYQH hYf ESQGFjd aj GdefGgL GdJQHhjI GdLOjOI, heOi EHQGR GdeVGejf GdJQHhjI dGJaGb GdWGFa aj cJH GdefgLjI GdJQHhjI GdLOjOI, hCgOGa gPg GdCNjQI, GdJj SYJ Edi JMbjbgG ajeG jNU GdfXQI Edi GdYQH hEdi ESQGFjd NGUI, hCfg ef GdeaJQV Cf jchf hGVYhgG jeKdhf eNJda GdaFGJ GddHfGfjI(B. (3EYJeO GdefgL GdGSJbQGFj aj gPg GdOQGSI, EVGaI Edi JbfjI JMdjd GdeVehf dKdGKI cJH QFjSjI ef GdcJH GdeOQSjI GdeYJeOI aj GdefgGL GdQSej deGOJj GdJQHjI GdhWfjI hGdJfTFI GdeOfjI, GdLZQGajG, hGdJGQjN, GdCcKQ JeKjdkG Ydi eSJhi GdZfi HGdUhQ hGdeVGejf, ef GdeQMdI GdGHJOGFjI HOAkG ef GdUa GdChd Edi GdeQMdI GdKGfhjI Cj Edi GdUa GdKGdK KGfhj(B. (3HjfJ GdfJGFL Cf GdUQGY Mhd GdbVjI GdCe, ghjI dHfGf, hbVjI ESQGFjd COi Edi Ndb RYRYI hGfbSGe aj cd eG jeJ EdjgG HUdI, hYcS JThTkG hJNHWkG Ydi GdeSJhjGJ GdSjGSjI hGdKbGajI hGdJQHhjI GddHfGfjI, aGdCjOhdhLjG GdJj MceJ GdefGgL GdLOjOI hGdNdajI GdJQHhjI, EJSeJ HWGHY GdJShjI hMQUJ HWQhMGJgG hWQjbI eYGdLJgG Ydi Cf JQVj LejY GdCWQGa GddHfGfjI, aefge ef jYJHQ ESQGFjd HGdUOjbI hefge ef jYJHQgG GdcjGf GdZGUH hYOh GdYQH GdeTJQc, ceG hhQO Gdbdjd ef GdYfGhjf hGdYHGQGJ Mhd GdebGheI EQVGA ddaFGJ GdUOjbI(B. (3hYqHQJ cJH GdGLJeGYjGJ Yf GdKhGHJ GddHfGfjI dLgI EfJeGA dHfGf ddYGde GdYQHj, hEYJHGQg LRAG dG jJLRC efg, hGdJCcjO Ydi GdbhGSe GdYQHjI GdeTJQcI hVQhQI GdESJaGOI efgG dJMbjb GdJcGed GdYQHj hehGLgI GdeNGWQ(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Curricula; Curriculum; Israel; Israel; Political Socialization; Socialisation politique; (3GSQGFjds; (3GdJfTFI GdSjGSjIs; (3GdefGgLs